European Region Types: A Cluster Analysis of European NUTS 3 Regions - Christine Aumayr (European Regional Science Association (ERSA), 2006)
The motivation for the present empirical work arose from a practical problem: It seemed not to be justifiable to compare growth and productivity developments of the 6 Styrian NUTS 3 regions to national and European averages without regarding differences in region-specific factor endowments and economic structure. In order to find suitable benchmark region-types for the Styrian regions, a cluster analysis on the level NUTS 3 was conducted among 1100 European regions, incorporating information on the economic importance of the three main sectors in terms of relative employment and gross value added, as well as spatial information on the density and the accessibility of population. As a result, 11 region-types (3 urban and 9 non-urban) were identified. The paper then compares the development (1995-2002) of aggregate southern Styria to its region type "industrialized peripheral regions" and the capital region Graz to the group of "industrialized regional centers with surroundings" in terms of GDP and sectoral labour productivity growth.
Keywords: 330